Study of polymorphisms of UGT1A1 and DPYD genes in chemotherapy for colorectal cancer - N. N. Timoshkina; O. A. Bogomolova; I. A. Zhuzhelenko; S. N. Kabanov; E. A. Kalabanova; I. S. Mitashok; Ya. V. Svetitskaya; D. I. Vodolazhskii (Сибирский онкологический журнал)
Background. The personalized approach implies an individual choice of medicines and their doses for the patient, providing the most effective and safe pharmacotherapy. Objective: analysis of the frequencies of UGT1A1 and DPYD polymorphisms and comparison of genotyping data with irinotecan and 5-fluorouracil-induced toxicity, respectively.Materials and Methods. Venous blood of 94 Caucasian patients (46 men and 48 women, median age 61 years). The *6 and *28 UGT1A1 alleles were identified by pyrosequencing, and the *2А DPYD allele was identified by Real-time PCR.Results. The genotyping of 94 patients with colon cancer did not reveal the *2A SNP in the DPYD gene. The frequency rate of the *6 and *28 alleles of the UGT1A1 gene was 0.346 and 0.016, respectively. 24 % of patients receiving chemotherapy with 5-fluorouracil developed side effects associated with the circulatory system and the gastrointestinal tract. Hematological and nonhematological toxic reactions were noted in 48 % and 50 % of patients receiving irinotecan. Severe bilirubinemia was associated with the *28/*28 UGT1A1 genotype. The presence of a high-risk genotype (*28/*1, *28/*28 UGT1A1) correlated with the development of side effects (p=0.040).Conclusion. The absence of carriers of the *2А DPYD allele in the sample with a significant proportion of pronounced adverse toxic reactions to 5-fluorouracil causes the need for the inclusion of new polymorphisms of the DPYD gene in pharmacogenetic testing. The inclusion of genotyping of UGT1A1 polymorphisms into a complex of preliminary examination is advisable when planning treatment with irinotecan.